Blockchain Applications in Food Supply Chain Management Case Studies and Implications - Zhang, Chen.; Gong, Yu.; Brown, Steve (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book contributes to blockchain applications in food supply chain management from both theoretical and practical perspectives. By using the case study research method, it empirically investigates why and how food companies implement blockchain technology. Moreover, it proposes a conceptual framework based on the case findings and extant literature. The book provides empirical evidence to verify academic findings such as critical success factors and barriers. Furthermore, it identifies the implementation process to answer the 'how' question. Uniquely, it applies the innovation process model and the practice-based view (PBV) to studies on food supply chains and blockchain. Thus, building on the original model and theory, it enriches the theory on blockchain implementation, making it a valuable asset for all researchers and practitioners interested in blockchain adoption and food supply chain management.
Chapter 1 Introduction -- Chapter 2 Literature Review -- Chapter 3 Research Methodology -- Chapter 4 Within-Case Analysis - Beef Ledger -- Chapter 5 Within-case Analysis - W Company -- Chapter 6 Within-case Analysis - Fair Chain Chapter 7 Cross-case Analysis -- Chapter 8 Discussion -- Chapter 9 Implications and Conclusion.
Keywords: Business logistics; Production management; Food -- Safety measures; Blockchains (Databases).; Sustainability; Supply Chain Management; Operations Management; Food Safety; Blockchain; Sustainability